Similarity Solution for the Ernst Equation with Electromagnetic Fields - Halilsoy, Mustafa (Lettere Al Nuovo Cimento, Italian Physical Society, 1983)
Exact similarity solution is given for the Ernst equation coupled with electromagnetic fields in general relativity.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1007/BF02751182) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: general relativity; Ernst equation